PERANAN STRATEGIC LEADERSHIP TERHADAP COMPETITIVE POSITIONING MELALUI ORGANIZATION LEARNING PADA PERUSAHAAN NON MANUFAKTUR DI SURABAYA - Lydia Kartika Saputra (Business Accounting Review, 2015)
This study was accomplished to reveal the role of strategic leadership to competitive positioning through organization learning. Strategic leadership and organization learning owned and implemented within an organization can create even strengthen the competitive positioning of the organization. Through the dimensions each variable can indicate how far the role of strategic leadership and organization learning to competitive positioning.The analysis technique used was outer and inner model by using software PLS. The result of research showed that there was significant positive affect of strategic leadership to the organization learning, but the organization learning  had no affect on the company's competitive positioning. And there was positive but not significant of strategic leadership to competitive positioning.